The Role of Teacher Learning Leadership in Improving Students' Motivation to Learn Science at Muhammadiyah Junior High School - Afifah, Khoiri Yahya; Haryanto, Sigit; Fuadi, Djalal (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study aims to analyze in depth the role of Science Teacher Leadership (KPG) in efforts to improve student learning motivation at Muhammadiyah Junior High School. The background of this study is driven by the urgency of improving the quality of science learning, which is often considered difficult and abstract, as well as the importance of the role of teachers as instructional leaders in overcoming low student learning motivation. The approach used in this study is qualitative with a single case study. The location of the study is Muhammadiyah Special Program Junior High School Delanggu, with research subjects including 2-3 science teachers, 6-10 selected students, and the Deputy Principal for Curriculum as key informants. Data were collected through in-depth interviews, non-active participant observation during the learning process in the classroom, and documentation analysis (lesson plans, student scores). The data analysis technique used the interactive model of Miles, Huberman, and Saldana, with data validity checked through source and technique triangulation. The results showed that the learning leadership of science teachers at Muhammadiyah Junior High School played a significant and effective role in catalyzing student learning motivation, especially intrinsic motivation. This role was manifested through three main dimensions: (1) Defining a Relevant Learning Mission, in which teachers integrated science concepts with spiritual values and real life, providing deep meaning that triggered intrinsic motivation; (2) Managing Practice-Based Learning Programs, through the consistent use of experimental and demonstration methods, which successfully meet students' basic psychological needs for competence and autonomy; and (3) Creating a Positive and Supportive Learning Climate, which ensures that students feel safe to interact and make mistakes, thereby fulfilling their need for relatedness. The impact of KPG is clearly seen in changes in students' perceptions of science and increased active participation in class. The study concludes that the effectiveness of KPG lies in its ability to adapt to the institutional context and focus on meeting students' psychological needs. The practical implications of this study emphasize the importance of strengthening teacher training in experience-based instructional design and differentiated feedback techniques.